Are Patient-Reported Social Needs and the Social Vulnerability Index Associated With Physical Function in Orthopedic Surgery? - Bill Young; Sara L. Kemper; Derek F. Amanatullah; Loretta Chou; Michael J. Gardner; Serena S. Hu; Marc Safran; Robin N. Kamal (Orthopedics, 2026)
Background: A gap exists in understanding the association of health-related social needs (HRSN), social determinants of health, and patients' physical function after orthopedic surgery. In this study, we asked: (1) Are HRSN and the social vulnerability index (SVI) associated with each other, and (2) are HRSN and SVI associated with patients' physical function after surgery? Materials and Methods: We conducted a prospective study in a multispecialty academic orthopedic clinic from June 2024 to October 2024. We enrolled new adult patients who consented to participate and presented with an orthopedic condition. Patients completed the Accountable Health Communities HRSN Screening Tool to assess HRSN; and the Patient-Reported Outcome Measure Information System Physical Function 10a (PROMIS PF-10a), which measures a patient's self-reported physical function. We also used patient addresses to determine the SVI for each participant. The primary outcome was the association between HRSN and SVI. The secondary outcome was the association between HRSN or SVI and PROMIS PF-10a. Results: We enrolled 127 new patients. Housing and food were the most frequently reported unmet HRSNs, affecting 14 (11.0%) patients each. There was no significant association between HRSNs and SVI. HRSNs and SVI showed inverse correlations with PROMIS PF-10a scores (r = −0.30 and r = −0.32, respectively; P < .001 for both). Conclusion: The findings suggest that area-level social determinants of health and individual patient HRSNs may independently affect physical function in orthopedic patients, which should be reflected in screening tools.